Reinterpretasi dan Rekonstruksi Dongeng Jaka Tarub dalam Drama Karya Akhudiat: Sebuah Pembacaan New Historicism - Lina Meilinawati Rahayu; Aquarini Priyatna; Rasus Budhyono (SUAR BETANG, 2019)
The paper examines the transformation of “Jaka Tarub”, a folktale contained in Babad Tanah Jawi, into the play Jaka Tarub by Akhudiat. Jaka Tarub by Akhudiat is a two-act play that is parodic in style. The play won the 1974 Jakarta Arts Council Playwriting Competition. The aim of the paper is to study how the tale is interpreted and reconstructed into Indonesian contemporary literature. The transformation of the tale is analyzed from a new historicist perspective. The analysis suggests that the history of a nation can be read through its literature since New Historicism sees that texts and history are always, inevitably, interrelated. Based on such a perspective, there is no longer such a thing as a single absolute “historical reality”. Instead, there are always different versions and perspectives to history. Akhudiat’s reinterpretation and reconstruction of the folktale represents Indonesia in the 1970s. Seen in this light, an Indonesian literary text that reflects history can be regarded as another version of history. Thus, New Historicism offers an appropriate approach to study such a literary text because it is through a New Historicist approach to reading that realities unwritten in mainstream texts of history become accessible to the reader or audience.